Enhancing Engineering Education: Exploring the Impact of Problem-Based Learning on Freshman Students' Skills and Engagement – A Case Study - Naik, Santosh Madeva; Bandi, Surendra; Lokeshwar Reddy, Ch. (Journal of Engineering Education Transformations, 2025)
This paper examines the impact of problem-based learning (PBL) on freshman engineering students' academic performance, technology enhancement, and leadership skills. With contemporary students gravitating less towards traditional classroom teaching, the study investigates the effectiveness of PBL in engineering education, focusing on learning outcomes and the perceptions of students and faculty members. Through design thinking, PBL is implemented, engaging students in real-world problem-solving and team activities. Results indicate significant improvements in student performance, teamwork, multidisciplinary knowledge, and faculty development. With attendance rates soaring above traditional levels, students recommend broader adoption of PBL across all classes. The study features PBL's efficacy in enhancing skills and knowledge while benefiting faculty multidisciplinary expertise and leadership. The study is taken up on the freshmen engineering students at an Indian college with respect to their experience with problem-based learning (PBL) method. The aim of this case study is to investigate the effectiveness of PBL in engineering education by examining the impact on student learning outcomes and also explore the perceptions and experiences of both students and faculty members. The study attempts to answer the following questions. 1. Does the incorporation of PBL enhance the quality of student learning outcomes, achieving higher levels of critical thinking, problem-solving skills, and creativity? 2. To what extent is the integration of PBL courses appropriate and effective in enhancing the learning experience of freshman engineering students at the entry level? For PBL implementation design thinking is followed. The approach to implementing problem-based learning (PBL) begins with structured activities like brainstorming and role-playing, inculcating teamwork and problem comprehension among students. Real-world contexts, such as nearby villages and non governmental organizations (NGOs), are integral to the approach, allowing students to identify authentic, real-time problems and ground their learning in practical scenarios. End-user involvement ensures that student solutions align with genuine needs, raising a sense of ownership and responsibility. Faculty members play a key role, drawing upon diverse technical knowledge and leadership skills to guide students effectively and undergo professional development themselves. The approach emphasizes experiential learning, collaborative problem-solving, and real-world application to cultivate technical competencies, critical thinking, creativity, and leadership skills among freshman engineering students. Reflections gathered through the Driscoll model revealed significant improvements in student performance and engagement. Attendance rates in PBL classes exceeded traditional levels, indicating participation. heightened student enthusiasm and Students reported enhanced teamwork, multidisciplinary knowledge, leadership skills, problem-solving abilities, and creativity. Notably, students expressed a preference for PBL classes, advocating for broader adoption across all courses. Faculty members also benefited, gaining multidisciplinary technical knowledge and leadership skills through their involvement in the PBL approach. The study highlights the effectiveness of problem-based learning (PBL) in improving student skills, knowledge, and engagement. Elevated attendance rates and positive student feedback support the efficacy of PBL in building critical thinking, creativity, and teamwork. The recommendation for broader adoption of PBL across all classes suggests its potential to enhance conceptual understanding and student learning experience. Additionally, faculty members' development of multidisciplinary technical knowledge and leadership skills further highlights the benefits of the PBL approach. The findings affirm PBL as a valuable pedagogical strategy for enhancing engineering education and student outcomes.